The Effects of Incentives, Workload and Intrinsic Motivation on Employee Performance at CV AISWA Palembang - Yahyu Nadillah; Firdaus Sianipar; Dian Septianti (Riset Anak Bangsa, 2026)
This study aims to analyze the effects of incentives, workload, and intrinsic motivation on employee performance at CV AISWA Palembang. A quantitative explanatory research design was employed. The study population consisted of 50 employees, all of whom were included in the sample using saturated sampling (census sampling). Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics version 26. The results show that the research instruments met the validity and reliability criteria and that the regression model satisfied the classical assumptions. Simultaneously, incentives, workload, and intrinsic motivation had a statistically significant effect on employee performance. Individually, each of the three variables had a positive and statistically significant effect on employee performance. The coefficient of determination indicates that the three independent variables explained 81.5% of the variation in employee performance, while the remainder was attributable to factors outside the research model. The study concludes that improving the incentive system, managing workloads proportionately, and strengthening intrinsic motivation can support higher employee performance at CV AISWA Palembang.